Frequency of Gastrointestinal Parasites, Anemia, and Nutritional Status among Children from Different Geographical Regions of Bolivia - Ceilan Apaza; Washington Cuna; Froilán Brañez; Roberto Passera; Celeste Rodriguez (Journal of Tropical Medicine)
The study aimed to measure the frequency of occurrence of infections with helminths, protozoa, and risk factors of undernutrition and anemia among schoolchildren from the Bolivian highland (altiplano) and lowland (subtropical) rural regions, with a high frequency of gastrointestinal parasite infections. Cross-sectional data were collected from 790 children, 5–13 years old. Microscopic examination of stool using the Ritchie technique, hemoglobin testing using the HemoCue analyzer, and anthropometric measurements were performed. Over 60% and 20% of children were infected with protozoa and helminth parasites, respectively. Infections caused by pathogenic Hymenolepis nana (15.7–5.2%), Ascaris lumbricoides (41.9–28.5%), Giardia lamblia (30.1–11.2%), Entamoeba histolytica (5.7–0.7%), and nonpathogenic Entamoeba coli (48.9–16%), Blastocystis hominis (40.2–28.5%), Iodamoeba butschli (16.1–2.5%), Chilomastix mesnili (19.2–7.3%), and Entamoeba histolytica/dispar (7.4–5.5%) parasites, were more prevalent in the highlands than the lowlands. Single parasitic infections were more prevalent in the lowlands; polyparasitism of light or heavy intensity predominated in the highlands. A strongly increased risk of anemia and a low prevalence of wasting were determined in children in the highlands. A higher risk for stunting was associated with children of older age, and a low burden of intestinal helminths would prevent wasting in children of highlands. Infections with A. lumbricoides and G. lamblia pathogens in older children were not significant covariates for stunting. Environmental, nutritional, and parasitic factors may predispose to anemia in the highlands. A nutritional intervention and parasite control effort will substantially improve children´s health in the highlands.